Corporate Legal Responsibility: A Levinasian Perspective - Soares, Conceição (Journal of business ethics, 2008)
In this article I will look into Corporate Legal Responsibility taking into account Levinas’s notion of infinite responsibility, as well as his understanding of ethical language. My account of Levinas’s philosophy will show that it challenges – breaking down – deeply entrenched distinctions in the dominant strands of moral philosophy, within which the theory of individual responsibility is embedded, such as between:(1) duty to others on the one hand and supererogation on the other; (2) perfect duty to others on the one hand and imperfect duties to others on the other; (3) insiders and outsiders; kith and kin on the one hand and strangers on the other; Levinas’s moral vision is an inclusive one which embraces all of humanity (at least of those present today) irrespective of historical, linguistic, cultural differences and diversities. In other words, each has responsibilities for and duties towards all others. Of course, one might say that there is nothing new about a universalising ethics – after all Kantianism, liberalism as well as utilitarianism are well known instances. However, more crucially, all these traditional moral philosophies uphold the theory of individual responsibility, which is rooted in the philosophy of individualism. Such a philosophy can make sense only of the concept of individual moral/legal agency but not corporate agency. Therefore, in this article I will attempt to show that the Levinasian vision is able to help us change our view with respect to corporate responsibility.